Pipsqueak: Lean Lambdas with Large Libraries - Oakes, Edward; Yang, Leon; Houck, Kevin; Harter, Tyler; Arpaci-Dusseau, Andrea C.; Arpaci-Dusseau, Remzi H. (International Conference on Distributed Computing Systems Workshops, 2017)
Microservices are usually fast to deploy because each microservice is small, and thus each can be installed and started quickly. Unfortunately, lean microservices that depend on large libraries will start slowly and harm elasticity. In this paper, we explore the challenges of lean microservices that rely on large libraries in the context of Python packages and the OpenLambda serverless computing platform. We analyze the package types and compressibility of libraries distributed via the Python Package Index and propose PipBench, a new tool for evaluating package support. We also propose Pipsqueak, a package-aware compute platform based on OpenLambda.